2003
DOI: 10.1039/b211246a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modulation of metalloprotein electron transfer at bare gold

Abstract: Engineered metalloproteins and enzymes can be self assembled on pristine gold electrodes in robust, electrochemically-addressable, arrays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…The properties of metalloprotein assemblies can be studied by a variety of methods, including those based on electrochemistry (Gaigalas and Niaura, 1997;Chi et al, 2001;Davis et al, 2003;Armstrong et al, 1997), photochemistry (Pascher et al, 1996;Gray, 2003) and scanning probe microscopy, SPM (Colton et al, 1997;Davis et al, 2000;Davis and Hill, 2002;Zhang et al, 2002). Scanning probe analyses (including scanning tunnelling microscopy, STM, and atomic force microscopy, AFM) are interesting because they allow us to study molecules individually, without the averaging inherent in most other forms of analysis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of metalloprotein assemblies can be studied by a variety of methods, including those based on electrochemistry (Gaigalas and Niaura, 1997;Chi et al, 2001;Davis et al, 2003;Armstrong et al, 1997), photochemistry (Pascher et al, 1996;Gray, 2003) and scanning probe microscopy, SPM (Colton et al, 1997;Davis et al, 2000;Davis and Hill, 2002;Zhang et al, 2002). Scanning probe analyses (including scanning tunnelling microscopy, STM, and atomic force microscopy, AFM) are interesting because they allow us to study molecules individually, without the averaging inherent in most other forms of analysis ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, site-directed mutagenesis studies have implicated the involvement of four lysines on pseudoazurin (in a ring around the type-I Cu centre) and glutamate/aspartate residues on NiR (around the type-I centre) in docking. [23,24] Though recent work has demonstrated that azurin and its mutants can be self-assembled on gold electrodes in orientation-specific electrochemically addressable arrays [8,9,25] we have sought here to maintain maximum orientational flexibility (in the first instance) by carrying out voltammetric studies in the fluid (diffusive) phase. As mentioned, many important developments have been made in generating "biocompatible" electrode interfaces at which metalloprotein voltammetry can be robustly observed.…”
Section: Introductionmentioning
confidence: 99%
“…Though the protein surface itself can be chemically or genetically modified in order to facilitate electron exchange at "bare electrodes" [8,9] in general, it is the electrode surface which is modified. Specifically, an attempt must be made to chemically generate a "biocompatible interface" with which the protein is able to reversibly and nondestructively interact.…”
Section: Introductionmentioning
confidence: 99%
“…Site-directed mutagenesis has been used to introduce cysteine residues on the surface of blue copper proteins (azurin and plastocyanin), thus facilitating protein chemisorption on unmodified gold. [212][213][214][215] When this strategy was used to promote direct ET to a surface cysteine mutant of Alcaligenes faecalis copper-containing nitrite reductase, only poor catalytic activity could be detected (although some noncatalytic signals were observed); 216 pyrolytic graphite edge eventually proved to be a better choice for studying this enzyme. 167,185 In contrast, cytochrome c nitrite reductase (ccNiR) retains activity when it is immobilized onto an unmodified Au(111) surface.…”
mentioning
confidence: 99%